SSU video episodes and implementation of CSA technology packages in key value chains communications campaign - Homann-Kee Tui, Sabine; Pele, Winnie; Ngwira, Amos; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report presents Shamba Shape Up (SSU) video episodes and implementation of CSA technology packages in key value chains communications campaign in Zambia. To scale up climate delivery systems, several platforms (mobile phones, the internet, radio, and television) were used, leveraging their benefits.